The Interaction Patterns Teachers and Students in Online Learning of Islamic Education Subjects - Hidayatur Rohmah; Muhammad Nasrullah (LPPM Universitas KH. A. Wahab Hasbullah, 2022)
During the Covid-19 pandemic, almost all Indonesian educational institutions adopted online learning. Departing from this phenomenon, there will be an assumption that in order for the learning process to run well, it is necessary to create a good pattern of interaction between teachers and students. In this study, the authors formulate how the interaction pattern of teachers and students in online learning PAI learning in the VIII grade curriculum at Al-Ittihad Junior High School Mojowarno Jombang. And what are the supporting and inhibiting factors of teacher and student interaction in online learning PAI learning in the VIII grade curriculum at Al-Ittihad Superior Junior High School Mojowarno Jombang. By using a qualitative descriptive approach, the researcher was directly involved in the research. This study suggests that: The importance of teacher and student interactions in the learning process makes a teacher need to play an active role in the use of time, in the learning process the teacher raises the interaction between the teacher and students for the purpose of learning, the interaction between teachers and students must be present and well developed so that the learning process runs well, when there are students who deviate, the teacher must be able to understand how to awaken students, the interaction pattern of teachers and students in online learning PAI learning in the VIII grade curriculum at Al-Ittihad Junior High School Mojowarno Jombang is a teacher-centered interaction pattern. Schools facilitate wifi for teachers as a means to provide online learning materials as long as teachers are still in the school environment as a supporting factor while the inhibiting factors are inadequate internet networks and good learning media and inadequate internet connection hosts.